A COMPREHENSIVE ANALYSIS OF THE DRIVERS AND ASSESSMENT METHODS OF FOREIGN DIRECT INVESTMENT ATTRACTION (World Economics and Finance Bulletin, 2025)
This study offers a comprehensive assessment of the macroeconomic, institutional, infrastructure, market, and geopolitical factors that shape the attraction of foreign direct investment (FDI). Applying System-GMM, AHP, TOPSIS, and DEA techniques, we examine 40 indicators for 20 countries over 2015-2024. The findings highlight the decisive contribution of institutional quality and infrastructure, while underscoring the adverse effects of inflation and geopolitical uncertainty. Using Uzbekistan as a case study, we demonstrate that enhancing resource efficiency by 16 percent and expanding “green” energy capacity could significantly boost high-value FDI inflows.